Prevalence of Digital Eye Strain and Computer Vision Syndrome (CVS) Among Radiologists: A Survey-Based Cross-Sectional Study - Fazal, Maham; Asghar, Asfandyar; Haq, Rana Intisar Ul; Qureshi, Wali Waqar (Journal of Rawalpindi Medical College, 2026)
Objective: To determine the prevalence of Digital Eye Strain (DES)/Computer Vision Syndrome (CVS) among radiologists and evaluate associated risk factors. Methods: A cross-sectional study was conducted across multiple cities of Pakistan from January to April 2025. A reliable and validated CVS questionnaire was distributed among radiology physicians to assess the symptoms of CVS. Risk factor assessment was done by acquiring relevant demographic and ocular health-related information, as well as data on the workplace environment and ergonomics. Non-parametric methods were employed for both univariate and multivariate analyses in order to determine associations between CVS score and various demographic and health-related variables. Results: Out of 242 participating radiologists, 44.6% were males and 55.4% females. The overall prevalence of CVS was 56.6%. The most frequently reported symptoms were headache (73.4%), worsening of eyesight (59.1%), and heavy eyelids (57.9%). Higher CVS scores were significantly associated with postgraduate residents, longer daily working hours, and fewer work breaks. Frequent breaks and older age were identified as protective factors. Conclusion: CVS is a prevalent occupational hazard among radiologists in Pakistan, closely linked to extended digital screen time and work-related demands. Addressing modifiable risk factors can help reduce symptom burden and improve radiologists' comfort and diagnostic performance. Keywords: Computers, Eyestrain, Occupational Diseases, Radiologists, Picture Archiving and Communication Systems.